How well is the National Cervical Screening Program performing for Indigenous Australian women? Why we don't really know, and what we can and should do about it. (19th September 2014) - Whop, L.J.; Cunningham, J.; Condon, J.R.
<x xml:space="preserve">Abstract</x> Since its inception in 1991, Australia's organised approach to cervical screening, the National Cervical Screening Program (NCSP), has seen a 50% reduction in both incidence and mortality from cervical cancer in Australia. However, Indigenous Australian women continue to experience a disproportionately higher burden of cervical cancer. No national data on screening participation of Indigenous women currently exist, in large part because pathology forms, the primary source of data for Pap Test Registers (PTR), do not record Indigenous status. While including Indigenous status on pathology forms is the obvious solution for producing essential information about cervical screening of Indigenous women, this will require an appropriate consultative process and it will be many years before reliable data are available. One interim option being explored is the feasibility of linking the PTR to another data source which includes Indigenous status, such as hospital data. However, despite its promise, there remain major impediments to obtaining useful linked data in Australia, and it continues to be unclear whether such an approach is viable for routine reporting. If we are to understand and improve cervical screening participation and outcomes for Indigenous women in the foreseeable future, Australia needs to act now to include Indigenous status in pathology forms and (subsequently) PTRs.